In vitro maturation of domestic cat oocytes subjected to different incubation times (Research, Society and Development, 2021)
The aim of this study was to evaluate the effect of three different incubation times on in vitro maturation of domestic cat oocytes. Thus, ovaries (n = 42) were submitted to slicing procedure and the oocytes recovered were classified; only good quality oocytes (Grade I and II) underwent in vitro maturation for three different periods (24 vs. 30 vs. 36 h) in supplemented TCM-99 medium. After, oocytes were evaluated for cumulus cell expansion and presence of the first polar body. After six replicates (7 ± 1,7 ovaries per replicate), a total of 334 viable oocytes were recovered. Differences (p